Cell-extrinsic consequences of epithelial stress: activation of protumorigenic tissue phenotypes - Fordyce, Colleen A (BioMed Central, 2012)
INTRODUCTION: Tumors are characterized by alterations in the epithelial and stromal compartments, which both contribute to tumor promotion. However, where, when, and how the tumor stroma develops is still poorly understood. We previously demonstrated that DNA damage or telomere malfunction induces an activin A-dependent epithelial stress response that activates cell-intrinsic and cell-extrinsic consequences in mortal, nontumorigenic human mammary epithelial cells (HMECs and vHMECs). Here we show that this epithelial stress response also induces protumorigenic phenotypes in neighboring primary fibroblasts, recapitulating many of the characteristics associated with formation of the tumor stroma (for example, desmoplasia). METHODS: The contribution of extrinsic and intrinsic DNA damage to acquisition of desmoplastic phenotypes was investigated in primary human mammary fibroblasts (HMFs) co-cultured with vHMECs with telomere malfunction (TRF2-vHMEC) or in HMFs directly treated with DNA-damaging agents, respectively. Fibroblast reprogramming was assessed by monitoring increases in levels of selected protumorigenic molecules with quantitative polymerase chain reaction, enzyme-linked immunosorbent assay, and immunocytochemistry. Dependence of the induced phenotypes on activin A was evaluated by addition of exogenous activin A or activin A silencing. In vitro findings were validated in vivo, in preinvasive ductal carcinoma in situ (DCIS) lesions by using immunohistochemistry and telomere-specific fluorescent in situ hybridization. RESULTS: HMFs either cocultured with TRF2-vHMEC or directly exposed to exogenous activin A or PGE(2 )show increased expression of cytokines and growth factors, deposition of extracellular matrix (ECM) proteins, and a shift toward aerobic glycolysis. In turn, these "activated" fibroblasts secrete factors that promote epithelial cell motility. Interestingly, cell-intrinsic DNA damage in HMFs induces some, but not all, of the molecules induced as a consequence of cell-extrinsic DNA damage. The response to cell-extrinsic DNA damage characterized in vitro is recapitulated in vivo in DCIS lesions, which exhibit telomere loss, heightened DNA damage response, and increased activin A and cyclooxygenase-2 expression. These lesions are surrounded by a stroma characterized by increased expression of α smooth muscle actin and endothelial and immune cell infiltration. CONCLUSIONS: Thus, synergy between stromal and epithelial interactions, even at the initiating stages of carcinogenesis, appears necessary for the acquisition of malignancy and provides novel insights into where, when, and how the tumor stroma develops, allowing new therapeutic strategies.